Governance of flood disaster management: Malaysian case study - J., Saifulsyahira; M. A., Edre; A. F., Ahmad Farhan; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2016)
Flood is a yearly event in Malaysia but surprisingly there is no law specifically to address it and the related issues. However there are many other laws, rules and regulations that are in force and these can be applied directly and indirectly to address flood issues. The custodian of these laws is not that of one Government department only, but designated to many different departments, each with its own responsibilities and functions. Managing floods therefore requires good inter-agency coordination and cooperation. This is not often easy but the Federal and State administrative culture, traditions and practices have evolved such that there is respect and understanding on the need to approach flood problems in an integrated manner. Flood governance entails the need of a coordinated system in dealing with this natural disaster. A significant lives and properties are lost each year due to increasing magnitude of flood, made worst by extreme climate change. Some of the countries choose decentralized flood governance management including Malaysia. However, it is still unclear whether decentralized or centralized flood management governance is more effective. This review was to compare between countries on governance of flood management. A mini scoping systematic review was done, where five articles with six different country examples were chosen for the review. Four out of six countries opted for decentralized flood governance as being more effective, as it leads to better democracy, local actors have a bigger role to play, more sophisticated technology and better training, privatization of necessities such as water supply helps to ease the central government burden and flood risk maps are built for predictive modelling and preventive action. However, lack of coordination remains an issue in all of the countries that could potentially be tackled using the COBIT framework. Further researches are needed to test the effectiveness of this framework in improving flood governance.